Best Hand I Ever Played, The: 52 Winning Poker Lessons From The World's Greatest Players - Steve Rosenbloom
Witty interviews with Doyle Brunson, Amarillo Slim, Phil Gordon, Annie Duke, and other outstanding professional poker players describe the greatest hands of each player's career, along with professional tips, expert instruction, money-making tips, and more. Original.